An open web-based GIS service for biomass data in Finland - Lehtonen, Eeva; Anttila, Perttu; Hakala, Kaija; Luostarinen, Sari; Lehtoranta, Suvi; Merilehto, Kirsi; Lehtinen, Harri; Mäntylä, Virpi; Maharjan, Anil; Niemeläinen, Oiva; Kolehmainen, Mikko (Elsevier, 2024)
Reliable, up-to-date biomass data are needed for climate change mitigation and resource efficiency. Therefore, a calculation and reporting tool with thematic maps and data was developed. A free web-tool, Biomass Atlas, collects the spatial distribution of biomasses in Finland. Over 300 data layers present land use, cultivation, residual biomasses from forest, crop production, animal husbandry, municipalities, and industry at 1 km2 spatial resolution. The service enables calculations of biomass amount in a defined geographical area of interest and examining the opportunities and restrictions to utilise biomasses. The service was evaluated with six test-users in laboratory tests and 20 voluntary pilot test-users. Biomass Atlas shows the regional potential of biomaterials, fertilizer products, and renewable energy, as well as potential targets for utilized, recyclable biomass. Other possible uses include monitoring plant cover on fields and assessing land use diversity. Application enables users with no experience in GIS or biomass assessments to analyse biomass resources, produce maps and data summaries for decision making.
Keywords: Agricultural biomass; Biodegradable waste; Thematic mapping; Database; manure; field crops; land use; biowaste; geographic information systems; Spatially explicit web-based application; Forest biomass